Odmiany wywiadu-rzeki (na wybranych przykładach) - Worach, Jolanta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
In the Polish language, there exists the expression “interview-river” meaning a very long interview draining the subject to the greatest possible depth. The article Varieties of Interview-river on given examples covers the analysis of three chosen interview-rivers with three different people. The interviews were discussed in reference to the following aspects:• interview structure• determination of its thematic variety• nature of questions• interviewer – interviewee interactionThe conclusions present what is interview-river and what it is characterised by. The aim of this article is to pinpoint the interview-river’s generic features and its functions.